A community jury study exploring the public acceptability of using risk stratification to determine eligibility for cancer screening. (8th May 2022) - Dennison, Rebecca A.; Boscott, Rachel A.; Thomas, Rae; Griffin, Simon J.; Harrison, Hannah; John, Stephen D.; Moorthie, Sowmiya A.; Morris, Stephen; Rossi, Sabrina H.; Stewart, Grant D.; Thomas, Chloe V.; Usher‐Smith, Juliet A.
Abstract: Introduction: Using risk stratification to determine eligibility for cancer screening is likely to improve the efficiency of screening programmes by targeting resources towards those most likely to benefit. We aimed to explore the implications of this approach from a societal perspective by understanding public views on the most acceptable stratification strategies. Methods: We conducted three online community juries with 9 or 10 participants in each. Participants were purposefully sampled by age (40–79 years), sex, ethnicity, social grade and English region. On the first day, participants were informed of the potential benefits and harms of cancer screening and the implications of different ways of introducing stratification using scenarios based on phenotypic and genetic risk scores. On the second day, participants deliberated to reach a verdict on the research question, 'Which approach(es) to inviting people to screening are acceptable, and under what circumstances?' Deliberations and feedback were recorded and analysed using thematic analysis. Results: Across the juries, the principle of risk stratification was generally considered to be an acceptable approach for determining eligibility for screening. Disregarding increasing capacity, the participants considered it to enable efficient resource allocation to high‐risk individuals and could see how it might help to save lives. However, there were concerns regarding fair implementation, particularly how the risk assessment would be performed at scale and how people at low risk would be managed. Some favoured using the most accurate risk prediction model whereas others thought that certain risk factors should be prioritized (particularly factors considered as non‐modifiable and relatively stable, such as genetics and family history). Transparently justifying the programme and public education about cancer risk emerged as important contributors to acceptability. Conclusion: Using risk stratification to determine eligibility for cancer screening was acceptable to informed members of the public, particularly if it included risk factors they considered fair and when communicated transparently. Patient or Public Contribution: Two patient and public involvement representatives were involved throughout this study. They were not involved in synthesizing the results but contributed to producing study materials, co‐facilitated the community juries and commented on the interpretation of the findings and final report.